A Novel Definition of L-Fuzzy Lattice Based on Fuzzy Set - Jun-Fang Zhang (The Scientific World Journal)
The concept of L-fuzzy lattice is presented by means of an L-fuzzy partially ordered set. An L-fuzzy partially ordered set A is an L-fuzzy lattice if and only if one of A[a], A[a], and A(a) is a lattice.